(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Food powders made from vegetables can be used as standalone dishes, additives to soups, sauces, salads, baked goods, beverages, etc. They can also be used as raw materials for the production of such products as chips, slices, mixes, granules. The purpose of the article was to develop a plant for drying plant material and to propose areas of use for food powders based on the analysis. The article discusses the classification and uses of food powders, analyses the market for vegetable powders. The main problems in the production of powders from vegetable raw materials are identified. The following main problems have been allocated, which may be the topics for further research: economic, environmental, resource efficiency, product quality, and equipment design complexity. It is noted that a high level of thermal impact on raw materials during processing determines the main disadvantages of production: energy consumption of equipment, duration of the technological process, loss of volatile aromatic and flavour components. The main advantages of the developed plant are: intensification of the process and reduction of the drying time of vegetable pomace due to the use of vibration. This leads to a constant renewal of the dried surface, and the vacuum in the apparatus affects the quality of the product, namely the product is concentrated at low temperature. The use of vacuum makes it possible to significantly intensify the dehydration process. The use of vegetable pomace as a raw material to be dried proved that the design features of the developed plant allow to obtain a high quality final product. As a result, a vacuum drying unit using vibration was developed. The plant is designed for drying under vacuum and mixing with vibration in the preparation of a wide range of dried products based on various raw materials. Vegetable (carrot, beetroot) pomace and spicy and aromatic herbs were used in the research. The main technical characteristics of the developed installation for the drying process are presented.